2011
DOI: 10.1097/shk.0b013e318204c106
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Post-Cardiac Arrest Care Bundle Including Therapeutic Hypothermia and Hemodynamic Optimization in Comatose Patients with Return of Spontaneous Circulation After Out-of-Hospital Cardiac Arrest

Abstract: Patients who present to the emergency department (ED) with return of spontaneous circulation after cardiac arrest generally have poor outcomes. Guidelines for treatment can be complicated and difficult to implement. This study examined the feasibility of implementing a care bundle including therapeutic hypothermia (TH) and early hemodynamic optimization for comatose patients with return of spontaneous circulation after out-of-hospital cardiac arrest. The study included patients over a 2-year period in the ED a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…85 Coronary artery disease is the most common trigger for out-of-hospital cardiac arrest and is identified in at least two thirds of patients who are resuscitated and undergo coronary angiography. 61 Twelve-lead ECG should be performed immediately after return of spontaneous circulation in the absence of an obvious noncardiac cause to identify ST-segment elevation myocardial infarction, which 79 Walters et al, 80 and Sunde et al 81 (Adapted from Jentzer et al 52 Used with permission.) is found in 25% to 30% of patients resuscitated from outof-hospital cardiac arrest.…”
Section: Interventionsmentioning
confidence: 98%
See 1 more Smart Citation
“…85 Coronary artery disease is the most common trigger for out-of-hospital cardiac arrest and is identified in at least two thirds of patients who are resuscitated and undergo coronary angiography. 61 Twelve-lead ECG should be performed immediately after return of spontaneous circulation in the absence of an obvious noncardiac cause to identify ST-segment elevation myocardial infarction, which 79 Walters et al, 80 and Sunde et al 81 (Adapted from Jentzer et al 52 Used with permission.) is found in 25% to 30% of patients resuscitated from outof-hospital cardiac arrest.…”
Section: Interventionsmentioning
confidence: 98%
“…51,52 Observational studies suggest that early 75 Sutherasan et al, 77 and Geri et al 86 hemodynamic optimization as part of a postarrest care bundle can improve outcomes, analogous to management of septic shock ( Figure 4). 52,[79][80][81] Patients often require fluid resuscitation after return of spontaneous circulation, although this should be guided by measures of preload responsiveness and intravascular volume status to avoid volume overload. 51,52,76 Hypotension refractory to fluids typically responds to vasopressors.…”
Section: Interventionsmentioning
confidence: 99%
“…Walters et al implemented a care bundle that included TTM and hemodynamic optimization targets 147 . In a pre-post design of 55 patients, the implementation of the care bundle was associated with a trend towards reduced mortality and improved neurological outcome.…”
Section: Quality Of Evidence: Low Strength Of Recommendation: Conditimentioning
confidence: 99%
“…The implementation of institution-specific standardized protocols, order sets, and a bundled care approach have proven a successful method in combating the barriers to implementation of therapeutic hypothermia [14][15][16][17][18][19][20] and were associated with an increased efficiency in achieving target temperature. 21,22 The effectiveness of a surgical safety checklist on rates of postoperative death and complications was documented by Haynes et al, 23 who reported a decrease in death rate and complication rate after implementation of a checklist.…”
Section: Recommendations For the Use Of Checklistsmentioning
confidence: 99%
“…Relying on a standardized protocol improves the quality and outcomes of an intervention such as therapeutic hypothermia. 9,[16][17][18]20,22 Checklists have also been used as tools to increase the quality and safety in many industries and have gained popularity in health care. Checklists standardize the tasks that must be completed and provide a transparent framework to ensure protocol adherence, all while establishing a process to share information and support among caregivers.…”
Section: Planning the Intervention: Improving Therapeutic Hypothermiamentioning
confidence: 99%